Agama Saiber Dalam Game Virtual Reality “second life” - Yusrina Pradipta Andityarini (ALAMTARA: Jurnal Komunikasi dan Penyiaran Islam, 2018)
Departing from the theory that saiber space is the growth space for offline social interaction, the logical consequence is that there will be a large collection of individuals, communities, and networks that resemble communities in the real world. Where there are a group of people, surely there will also be rules, signs, symbols, ties, and procedures that govern social relations in cyberspace. The relation itself includes many fields, ranging from politics, business, literature, hobbies, gossip, to religion. It is not impossible, every social relationship or community that grows in the saiber space will emerge a rule whose indicators are unique and totally different from the real world. This essay will discuss the possibility of the emergence of cyberreligion by taking the example of a religious community born from the virtual reality game Condec Life. The theory of religion used in this essay takes the opinion of Emily Durkheim quoted in the book Religious Studies: The Making of a Discipline (Walter, 1995). Durkheim said that "religion is something eminently social" and "religious representations of collective representation which express collective realities". In other words, the reality constructed by social order and human collective consciousness is its main forming factor. Durkheim views religion as functioning and will continue to function to form knowledge formation. The collective consciousness of humans who are always thirsty for answers and knowledge is the source of the creation of moral values, cultural ideals, and religious aspirations.